Pelletized rice-straw biochar as a slow-release delivery medium: Potential routes for storing and serving of phosphorus and potassium. Issue 2 (April 2022) - Dinh, Van M.; Nguyen, Hue T.; Nguyen, Anh M.; Nguyen, Thuy T.; Nguyen, Thanh-Lan; Uteau, Daniel; Nguyen, Nam H.; Tran, Tien M.; Dultz, Stefan; Nguyen, Minh N.
Abstract: Recycling of straw in novel forms, e.g., slow release mediums, has increasingly gained attention. This study aimed to use rice straw for pellet fabrication and demonstrate the ability of pellets for slow delivery of phosphorus (P) and potassium (K). To increase the cohesiveness of the medium and to modify release properties, additions of diatomite and its mixture with bentonite were also tested. We fabricated three types of biochar pellets from different mixtures, i.e., 'straw and NaH2 PO4 ' (9:1); 'straw, NaH2 PO4 and diatomite' (8:1:1) and 'straw, NaH2 PO4, diatomite and bentonite' (8:1:0.5:0.5) that were correspondingly named as S-pellet, SD-pellet and SDB-pellet. The kinetic experiments have revealed the performance of the pellets in delaying P and K releases. In the first 2 weeks, P and K concentrations released from S-pellet, SD-pellet and SDB-pellet were exponentially increased up to 156 and 163, 107 and 77, 113 and 75 mg L −1, respectively. The released P amounts at this stage were equal to 83.9%, 74.7% and 79.9% of the total P contents while those of K were equal to 81.7%, 53.6% and 52.3% of the total K contents in S-pellet, SD-pellet and SDB-pellet, respectively. All the major constituents in the pellets (phytolith, diatomite, bentonite) revealed their mutual interdependencies in regulating the overall release rates of P and K. The effective performance of the pellets could be an indication for a simple method to create slow-release fertilizers that can eventually bring more incentives to farmers to change their way to handle straw towards more high-tech or sustainable practices. Graphical Abstract: ga1 Highlights: Rice straw was visualized as a composite of lignocellulose, phytolith and embedded nutrients. Pyrolyzation of rice straw at 600 °C enabled pellet fabrication. Pellets from pyrolized straw show slow-release properties for P and K. Amendments of pellets with diatomite and bentonite slowed down release rates for P and K.